PENERAPAN KAHOOT SEBAGAI MEDIA EVALUASI PEMBELAJARAN MATEMATIKA (MASA PANDEMI COVID-19) TERHADAP HASIL BELAJAR - Mugiarti Lestari; Bambang Priyo Darminto; Teguh Wibowo (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The purpose of this study was to determine the differences in mathematics learning outcomes between students usingmedia Kahoot and classes that did not usemedia Kahoot for class X MIPA at SMA Negeri 1 Petanahan in the 2020/2021 academic year during the Covid-19 pandemic. This research is included in the Quasi Experimental Research with Posttest Only Control Group Design. The sample amounted to 34, each in the experimental class and control class.media are used Whatsapp Group and Google Classroom to support distance learning (PJJ). This study used the experimental classmedia Kahoot in its evaluation, while the control class used conventional evaluation (Google Classroom). According to the results of the research, the data after treatment shows that the average value of the experimental class is 78.16176 and the control class has an average value of 59.11765. The data is calculated by means of hypothesis testing, namely the t-test with the results of tobs 7,286254 and DK of 1,669804. Calculations using SPSS at the stated significance value of 0.000 <0.05, it can be concluded that there is a significant difference between the experimental class and the control class.